Linfadenectomia inguinoilíaca videolaparoscópica em cadelas após impregnação com diferentes marcadores linfáticos - Souza, Fernando Wiecheteck de (2014)
Laparoscopic pelvic lymphadenectomy has been performed routinely in medicine, using injectable lymphatic markers for delineation of lymphatic tissue and promoting free surgical margins of resection in tumor tissues. This practice also has therapeutic and diagnostic purposes when the pelvic lymph nodes are tumor-chain, resulting in a better prognosis for patients with certain types of cancer. Lymphadenectomy also aids in the diagnosis of regional metastases in other organs as well as in establishing the type of therapy to be adopted in the immediate postoperative period. However, this procedure is seldom performed in veterinary medicine, and practically not applied in combination with laparoscopy. This work consists of three scientific papers, with the first two showing the authors' experience with the techniques of marking and lymphatic resection associated with breast neoplasms in clinical cases. The last document involves research with healthy animals without mammary neoplasms. The results allowed us to check the effectiveness of the technique of lymphatic markup for the chain of pelvic lymph nodes using the dyes (methylene blue and indocyanine green) in dogs, allowing the observation of lymph node regions on both sides to deep iliac vessels excised via laparoscopic lymphadenectomy and the effectiveness and safety of the surgical technique. We conclude that it is still necessary to conduct further studies aiming to delineate string pelvic lymph nodes of healthy animals and presenting breast neoplasms, to achieve the best results in relation to the technique of lymphatic marking the mammary glands of female dogs